Ghana : Selected Issues and Statistical Annex. (IMF Staff Country Reports; Country Report, 1996)
This Selected Issues paper and Statistical Annex examines the impact of cocoa taxation on cocoa supply in Ghana. The paper describes historical developments in cocoa production. The effects of the taxation of cocoa in Ghana are evaluated and a dynamic model of cocoa supply is estimated and used for simulations. The paper concludes that the most important factors adversely affecting the cocoa sector were government policies. Specifically, in the late 1960s and the 1970s, the effective cocoa duty rates were punitive and the cocoa sector was further hit by policies of overvalued exchange rate.